How to Feed a Horse: Understanding Basic Principles of Horse Nutrition - Edward L. Johnson; Kylee J. Duberstein (EDIS)
AN236, a 5-page fact sheet by Edward L. Johnson and Kylee J. Duberstein, discusses the nutritional needs of horses, common guidelines to observe when feeding one’s horse, and how to determine if a horse’s nutritional requirements are being met. Published by the UF Department of Animal Sciences, March 2010.